2006
DOI: 10.1088/0951-7715/19/8/011
|View full text |Cite
|
Sign up to set email alerts
|

Quaternions and particle dynamics in the Euler fluid equations

Abstract: Vorticity dynamics of the three-dimensional incompressible Euler equations are cast into a quaternionic representation governed by the Lagrangian evolution of the tetrad consisting of the growth rate and rotation rate of the vorticity. In turn, the Lagrangian evolution of this tetrad is governed by another that depends on the pressure Hessian. Together these form the basis for a direction of vorticity theorem on Lagrangian trajectories. Moreover, in this representation, fluid particles carry ortho-normal frame… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 51 publications
2
65
0
4
Order By: Relevance
“…Moreover, they show that the vorticity does not grow faster than double exponential in time, and the velocity field remains bounded up to T D 19, beyond the singularity time alleged in [16]. Finally, we mention the recent work of Gibbon et al (see [13] and the references therein), where they reveal some interesting geometric properties of the Euler equations in quaternion frames.…”
Section: Introductionmentioning
confidence: 80%
“…Moreover, they show that the vorticity does not grow faster than double exponential in time, and the velocity field remains bounded up to T D 19, beyond the singularity time alleged in [16]. Finally, we mention the recent work of Gibbon et al (see [13] and the references therein), where they reveal some interesting geometric properties of the Euler equations in quaternion frames.…”
Section: Introductionmentioning
confidence: 80%
“…Fluid particles not only take complicated trajectories but they also rotate in motion. Recent work has shown that Hamilton's quaternions are applicable to this type of problem [78,[100][101][102][103]. In his lifetime Hamilton's ideas did not meet with the approval of his contemporaries [104][105][106] but in the context of modern-day problems the crucial property that quaternions possess -that they represent a composition of rotations -has made them the technical foundation of modern inertial guidance systems in the aerospace industry where tracking the paths and the orientation of satellites and aircraft is critical [107].…”
Section: A Formulation In Quaternionsmentioning
confidence: 99%
“…Another example that could be cast into this format are the equations of ideal MHD in Elsasser form (see [78,100,101] although the existence of two material derivatives requires some generalization. In Section 5.3 it will be shown how the quartet in (35), based upon the pair of Lagrangian evolution equations (33) and (34), can determine the evolution of an ortho-normal frame for a fluid particle in a trajectory.…”
Section: A Class Of Lagrangian Evolution Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We present results for the Riccati equation. The special interest in this equation comes from the fact that it appears in the Euler vorticity dynamics (see [10]). …”
Section: Introductionmentioning
confidence: 99%